1997
DOI: 10.1007/s004360050317
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of genetically distinct strains of Enterocytozoon bieneusi

Abstract: Enterocytozoon bieneusi is the most frequently found microsporidium in human infections. In all, 3 distinct genotypes were detected in 12 stool samples from 8 patients with acquired immunodeficiency syndrome (AIDS). A total of 9 polymorphic sites were found in the 243-bp-long internal transcribed spacer (ITS) of the rDNA gene, whereas none was found in 241 bp of adjacent rRNA coding regions. The genotype was stable in samples taken during 11 weeks of infection from one of the patients. The existence of and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 9 publications
3
46
1
Order By: Relevance
“…Within subgroup 1b, four genotypes were found only in HIV-positive patients, in Peru, Thailand and Uganda, two genotypes were found only in animal, both in pet birds in Portugal, and one genotype named Peru 6 was found both in human in Peru and in animals, pet birds and a dog, both in Portugal (Leelayoova et al, 2006;Lobo et al, 2006b;Sulaiman et al, 2003a;Tumwine et al, 2002). Subgroup 1c contains seven genotypes that were found only in human (Breitenmoser et al, 1999;Breton et al, 2007;Espern et al, 2007;Leelayoola et al, 2005;Liguory et al, 2001;Liguory et al, 1998;Rinder et al, 1997;Sadler et al, 2002;Sulaiman et al, 2003a). One genotype named B appear to be prevalent in Europe while genotype A was found in four continents Europe, South America, Asia and Africa.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Within subgroup 1b, four genotypes were found only in HIV-positive patients, in Peru, Thailand and Uganda, two genotypes were found only in animal, both in pet birds in Portugal, and one genotype named Peru 6 was found both in human in Peru and in animals, pet birds and a dog, both in Portugal (Leelayoova et al, 2006;Lobo et al, 2006b;Sulaiman et al, 2003a;Tumwine et al, 2002). Subgroup 1c contains seven genotypes that were found only in human (Breitenmoser et al, 1999;Breton et al, 2007;Espern et al, 2007;Leelayoola et al, 2005;Liguory et al, 2001;Liguory et al, 1998;Rinder et al, 1997;Sadler et al, 2002;Sulaiman et al, 2003a). One genotype named B appear to be prevalent in Europe while genotype A was found in four continents Europe, South America, Asia and Africa.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Before this report, 14 ITS genotypes were known from humans (5 genotypes), pigs (6 genotypes), a cat (1 genotype), and cattle (2 genotypes) (1,13,(15)(16)(17)(18), but since no identical ITS genotypes of E. bieneusi were found in humans and animals its zoonotic potential was controversially discussed. In this report we investigated diarrheal fecal samples of another 26 humans and 350 animals from 37 species.…”
mentioning
confidence: 99%
“…Unfortunately, because the spores of E. bieneusi strains are morphologically indistinguishable and since this species cannot be cultured, traditional morphological, biochemical, and immunological methods are unavailable for strain differentiation. Instead, a genotypic method has been described to differentiate characteristic genotypes of the internal transcribed spacer (ITS) of the rRNA gene (rDNA) (16).…”
mentioning
confidence: 99%
“…Breitenmoser et al (1) demonstrated that E. bieneusi genotypes from animal origins were different from those originated from humans by comparing rDNA ITS sequences. To date, four different human-derived E. bieneusi genotypes, named A, B, C, and D, are known (1,10). In our patient the underlying E. bieneusi strain was identified as genotype C, which has been found previously only in HIV-positive patients (1,10).…”
Section: Molecular Diagnosis Of An Enterocytozoon Bieneusi Human Genomentioning
confidence: 60%